1999
DOI: 10.1037/0021-9010.84.5.786
|View full text |Cite
|
Sign up to set email alerts
|

Effects of justice conditions on discrete emotions.

Abstract: Research on organizational justice typically focuses on attitudinal, cognitive, or behavioral outcomes. Emotional reactions to justice have been suggested but not studied. The emotional appraisal literature provides a framework within which to analyze emotional reactions to just and unjust events. Undergraduates (67 females and 55 males) were randomly assigned to conditions crossing either a positive or negative outcome and a procedure which was either fair, biased in the participant's favor, or biased in favo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
448
1
21

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 548 publications
(502 citation statements)
references
References 43 publications
19
448
1
21
Order By: Relevance
“…Research has shown that such inequity perceptions produce strong negative emotional reactions (Folger & Cropanzano, 2001;Weiss, Suckow, & Cropanzano, 1999). Further, the presence of dysfunctional behavior might weaken within-team relations because members will likely lose trust in their disruptive teammates (cf.…”
Section: Dysfunctional Team Behavior and Negative Team Affective Tonementioning
confidence: 99%
“…Research has shown that such inequity perceptions produce strong negative emotional reactions (Folger & Cropanzano, 2001;Weiss, Suckow, & Cropanzano, 1999). Further, the presence of dysfunctional behavior might weaken within-team relations because members will likely lose trust in their disruptive teammates (cf.…”
Section: Dysfunctional Team Behavior and Negative Team Affective Tonementioning
confidence: 99%
“…Anger undoubtedly is often aroused when an external agent is viewed as having acted in an improper and disturbing manner (see Baron, Neuman, & Geddes, 1999;Weiss et al, 1999, in addition to the studies performed by appraisal theorists). However, there is good reason to think that the ordinary "person in the street" (to use Averill's, 1983, characterization) can become angry even when the aversive event is not regarded as "illegitimate."…”
Section: Frustration: Obstructing Goal Attainmentmentioning
confidence: 99%
“…No entanto, a injustiça parece conter mais intensamente aspectos emocionais visto que ela é freqüentemente associada ou considerada como um sentimento (Barclay, Skarlicki & Pugh, 2005;Weiss, Suckow & Cropanzano, 1999). Neste sentido pressupomos que há uma assimetria na intensidade dos componentes afetivos entre as representações sociais da justiça e injustiça.…”
Section: Organização Afetiva Das Representações Sociaisunclassified